Schneider's first rank symptoms and continuous performance disturbance as indices of dysconnectivity of left- and right-hemispheric components of language in schizophrenia. - Ceccherini-Nelli, A; Turpin-Crowther, K; Crow, T (2007)
BACKGROUND: Here we investigate pathophysiological dimensions (language disturbance, negative symptoms, lateralisation and the continuous performance test) in relation to ICD-10 and DSM-IV concepts of diagnosis. METHODS: A total of 32 consecutive psychotic patients with at least one Schneider's first rank symptom (SFRS), 15 depressed patients without SFRS and 17 normal volunteers were assessed with the Clinical Language Disorder Rating Scale (CLANG), SFRS, "pure defect" Huber's basic symptoms (HBS), handedness (Annett's pegboard task), and the A-X Continuous Performance Test (AX-CPT). RESULTS: CLANG total score (an index of severity of language disorder) was correlated with the severity of SFRS, a higher leftward shift of handedness, and poorer performance on AX-CPT. Receiver operating characteristic (ROC) analysis showed that only CLANG and AX-CPT variables had adequate predictive validity in separating cases of ICD-10 schizophrenia from other diagnoses. The logistic regression model predicting the presence of ICD-10 schizophrenia was statistically significant using CLANG and AX-CPT variables, but not SFRS or other variables. HBS did not correlate with other variables and did not predict ICD-10 diagnosis. CONCLUSIONS: A cross-sectional diagnosis based on language disturbance and CPT performance yields a diagnostic construct largely overlapping with the ICD-10 definition of schizophrenia. We suggest that Schneider's first rank symptoms (that play a large role in the DSM-IV concept) can be considered an index of left hemisphere dysconnectivity for language whereas CPT dysfunction reflects dysconnectivity of the right hemisphere for those remoter ("spatial") associations that are closer to Bleuler's core defect and to the chronicity implicit in the ICD definition. Thus the dimensions of language disturbance in psychosis can be traced to specific cortico-cortical dysconnectivities.